PSYCHOLOGICAL IMPACT FACTORS OF OPEN SPACES ON URBAN DWELLERS IN THE FEDERAL TERRITORY OF KUALA LUMPUR - Marlyana Azyyati, Marzukhi; Nur Masyitah, Ghazali; Oliver Ling, Hoon Leh; Yusfida Ayu, Abdullah; Muhammad Hakim, Danial; Khalid, Zanudin (Construction Research Institute of Malaysia (CREAM), 2025)
Mental health issues have many causes; in many cases, this includes the changing and unpredictable elements of open spaces. Therefore, this study addresses alternative approaches to determine the psychological causes among urban dwellers exposed to Coronavirus Disease in 2019 (COVID-19). The objectives are to examine the magnitude of psychological causes (depression, anxiety, and stress) and the associated factors of open spaces among urban populations who have been exposed to COVID-19. The research employs a quantitative method as the main method. In addition to the secondary data collection, the Urban Mental Health Questionnaires (UMHQ-DASS21) questionnaire survey is utilized. Stratified random sampling for a total of 241 samples was performed in PPR Pantai Ria, Lembah Pantai, Federal Territory of Kuala Lumpur. The areas are selected due to their classification as COVID-19 red zone areas during the Movement Control Order. The findings reveal that most of the respondents demonstrate the symptomatology of depression, anxiety, and stress based on the perception of open spaces. Meanwhile, the correlation analysis demonstrates a high correlation between the respondents’ psychological aspects and open spaces. The result of this research can benefit the Ministry of Health, Ministry of Housing and Local Government, and urban planning decision-makers to establish a new policy or improve the existing policies and guidelines that can mitigate the impacts of the complex dynamics of infectious diseases post-COVID-19.